High prevalence of Blastocystis sp. in farmed sika deer (Cervus nippon) in Northern China - Gao, Zhen-Qiu; Gao, Yang; Zhuang, Hong-Di; Bao, Guang-Rong; Liu, Jing; Li, Jian-Ming; Xue, Nian-Yu; Cao, Hong-Wei; Liu, Shuo (Frontiers in Veterinary Science, 2025)
IntroductionBlastocystis sp. is a widespread intestinal protist, that threatens the health of humans and animals. However, epidemiological data on Blastocystis sp. in sika deer are still scarce in China and globally. This study aimed to reveal the infection rate, and subtype distribution of Blastocystis sp. in farmed sika deer across China.MethodsA total of 466 fresh fecal samples were collected from farmed sika deer in northern China. A 600 bp fragment of the SSU rRNA was amplified to detect the presence of Blastocystis sp. in samples.ResultsThe results revealed an overall infection rate of Blastocystis sp. at 65.02% (303/466). The highest infection rate was found in Shandong (98%, 49/50), followed by Heilongjiang (95.51%, 85/89), while the lowest infection rate was found in Jilin (36.31%, 61/168). Additionally, within the seasonal group, the infection rate was significantly higher in autumn (69.04%) than in summer (43.06%). In the age group, although the infection rate in young animals (68.38%) was higher than in adults (63.90%), no statistical difference was observed. Ten subtypes were identified from 303 Blastocystis sp.-positive samples, including ST1, ST5, ST10, ST14, ST21, ST23, ST24, ST26, ST30 and ST42. Among these, ST10 was the dominant subtype with an infection rate of 43.23% (131/303), and ST1 and ST5 were zoonotic subtypes. Notably, this study is the first to report the presence of ST42 in sika deer.DiscussionThese findings suggest that sika deer may be a potential source of human Blastocystis sp. infection. In addition, this study reveals the high infection rate of Blastocystis sp. in farmed sika deer and reports for the first time the presence of ST42 subtype, providing valuable data for the epidemiological study of Blastocystis sp. in sika deer.